2017
DOI: 10.1371/journal.pone.0172829
|View full text |Cite
|
Sign up to set email alerts
|

Small rodents as paratenic or intermediate hosts of carnivore parasites in Berlin, Germany

Abstract: Rodents are important intermediate and paratenic hosts for carnivore parasites, including the important zoonotic agents Toxoplasma, Echinococcus and Toxocara. Monitoring of such parasites in rodents can be used to detect increasing risks for human and veterinary public health. Rodents were trapped at four sites in Berlin, two near the city center, two at the periphery. PCRs were conducted to detect Coccidia (target ITS-1) and specifically Toxoplasma gondii (repetitive element) in brain and ascarids (ITS-2) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 64 publications
4
29
0
Order By: Relevance
“…Under natural conditions it is most likely that adult wild carnivores become infected via rodents functioning as paratenic hosts. There is a good reason for this since T. canis DNA was detected in 8 (3.1%) out of 257 mice and voles captured in outskirt districts of Berlin city with high fox densities and, the T. canis ELISA seroprevalence in these small rodents added up to 14.2% [42]. The transplacental and transmammary infection explains why juvenile hosts in our study showed higher ascarid prevalence and burdens.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Under natural conditions it is most likely that adult wild carnivores become infected via rodents functioning as paratenic hosts. There is a good reason for this since T. canis DNA was detected in 8 (3.1%) out of 257 mice and voles captured in outskirt districts of Berlin city with high fox densities and, the T. canis ELISA seroprevalence in these small rodents added up to 14.2% [42]. The transplacental and transmammary infection explains why juvenile hosts in our study showed higher ascarid prevalence and burdens.…”
Section: Discussionmentioning
confidence: 52%
“…Mesocestoides tetrathyridia were found in mice and voles in Germany in the same low percentage as those of T. polyacantha and T. crassiceps [36]. In a more recent study, tetrathyridia were detected in six out of 257 small rodents in Berlin [42]. Considering this high prevalence in both raccoon dogs and red foxes, it has to be assumed that the life cycle of M. litteratus differs from the those of above mentioned Taenia species.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulties with finding larvae specimens in the tissues of intermediate/paratenic hosts (such as hu- mans) have led to the development of serological tests for use in toxocarosis diagnostics (Dziemian et al 2008;Fillaux and Magnaval 2013). Used on rodent hosts, these methods deduced a 14.2% T. canis seroprevalence and showed ELISA to be more sensitive than PCR for detecting infection with the parasite (Krucken et al 2017). Studies using immunodiagnostic methods have been carried out worldwide (Krucken et al 2017;Li et al 2017;Lassen et al 2016;Klockiewicz et al 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…Used on rodent hosts, these methods deduced a 14.2% T. canis seroprevalence and showed ELISA to be more sensitive than PCR for detecting infection with the parasite (Krucken et al 2017). Studies using immunodiagnostic methods have been carried out worldwide (Krucken et al 2017;Li et al 2017;Lassen et al 2016;Klockiewicz et al 2019a). Serological analysis also allows the easy detection of mixed infections in hosts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation